Tunjuk Ajar Melayu in Riau Malay syair: An ecocritical study - Ermawati S; Andayani Andayani; Nugraheni Eko Wardani (Studies in English Language and Education, 2026)
This study explores ecological values and environmental awareness embedded in the verses of Riau Malay syair (a traditional form of poetry) through an ecocritical lens. Syair, as a distinctive form of traditional Malay poetry, serves as a cultural vessel for moral guidance and collective memory. Employing a qualitative descriptive approach, this research drew on observational data and textual analysis. The primary sources consisted of two works by Tenas Effendy, from which lines of syair were selected as the research data. These data were examined using an interactive process that involved data reduction, data display, and conclusion drawing. The findings revealed that Malay elders and cultural leaders have long expressed concern for environmental issues in Riau by embedding ecological counsel, tunjuk ajar, within syair. The ecological values identified include advice, encouragement, prohibitions, and warnings related to environmental management and conservation. Environmental awareness is articulated through deliberate word choices that reflect ecological challenges faced by the community. From an ecocritical perspective, the results align with Garrard’s framework, with thematic categories emerging in the form of pollution, wilderness, apocalypse, animals, and the earth. These findings highlight the wisdom of the Malay community in upholding environmental balance. Beyond contributing to scholarly understanding of Tunjuk Ajar Melayu and Malay cultural heritage, this study also reinforces public awareness of the importance of environmental conservation.